Metformin is the key factor in elevated plasma growth differentiation factor‐15 levels in type 2 diabetes: A nested, case–control study. Issue 2 (2nd October 2018) - Natali, Andrea; Nesti, Lorenzo; Venturi, Elena; Shore, Angela C.; Khan, Faisel; Gooding, Kim; Gates, Phillip E.; Looker, Helen C.; Dove, Fiona; Goncalves, Isabel; Persson, Margaretha; Nilsson, Jan; et al.
Abstract : Produced as a tissue defence response to hypoxia and inflammation, growth differentiation factor‐15 (GDF‐15) is elevated in people receiving metformin treatment. To gain insight into the relationship of GDF‐15 with metformin and major cardiovascular risk factors, we analysed the data from the SUMMIT cohort (n = 1438), a four‐centre, nested, case–control study aimed at verifying whether biomarkers of atherosclerosis differ according to the presence of type 2 diabetes and cardiovascular disease. While in univariate analysis, major cardiovascular risk factors, with the exception of gender and cholesterol, increased similarly and linearly across GDF‐15 quartiles, the independent variables associated with GDF‐15, both in participants with and without diabetes, were age, plasma creatinine, N‐terminal pro‐brain natriuretic peptide, diuretic use, smoking exposure and glycated haemoglobin. In participants with diabetes, metformin treatment was associated with a 40% rise in GDF‐15 level, which was independent of the other major factors, and largely explained their elevated GDF‐15 levels. The relatively high GDF‐15 bioavailability might partly explain the protective cardiovascular effects of metformin.